Case Report: Secondary Hemophagocytic Lymphohistiocytosis With Disseminated Infection in Chronic Granulomatous Disease—A Serious Cause of Mortality - Squire, Jacqueline D.; Vazquez, Stephanie N.; Chan, Angela; Smith, Michele E.; Chellapandian, Deepak; Vose, Laura; Teppa, Beatriz; Hanson, I. Celine; Chinn, Ivan K.; Forbes-Satter, Lisa; Seeborg, Filiz O.; Nicholas, Sarah K.; et al. (Frontiers in Immunology, 2020)
Chronic granulomatous disease (CGD) is a primary immune deficiency due to defects in phagocyte respiratory burst leading to severe and life-threatening infections. Patients with CGD also suffer from disorders of inflammation and immune dysregulation including colitis and granulomatous lung disease, among others. Additionally, patients with CGD may be at increased risk of systemic inflammatory disorders such as hemophagocytic lymphohistiocytosis (HLH). The presentation of HLH often overlaps with symptoms of systemic inflammatory response syndrome (SIRS) or sepsis and therefore can be difficult to identify, especially in patients with a primary immune deficiency in which incidence of infection is increased. Thorough evaluation and empiric treatment for bacterial and fungal infections is necessary as HLH in CGD is almost always secondary to infection. Simultaneous treatment of infection with anti-microbials and inflammation with immunosuppression may be needed to blunt the hyperinflammatory response in secondary HLH. Herein, we present a series of X-linked CGD patients who developed HLH secondary to or with concurrent disseminated CGD-related infection. In two patients, CGD was a known diagnosis prior to development of HLH and in the other two CGD was diagnosed as part of the evaluation for HLH. Concurrent infection and HLH were fatal in three; one case was successfully treated, ultimately receiving hematopoietic stem cell transplantation. The current literature on presentation, diagnosis, and treatment of HLH in CGD is reviewed.